Pendampingan Pembelajaran dengan metode Project Based Learning dan Thematic Learning Model di Sekolah Alam Pangkalpinang - Dini Andriani; Vebtasvili Vebtasvili (Universita Bangka Belitung, 2023)
The Merdeka Learning Campus Merdeka Program(MBKM) is a program launched by the Minister of Education andCulture which aims to encourage students to master varioussciences in preparation for entering the world of work. One of theMBKM programs is Teaching Assistance Activities wherestudents go directly into the world of education under theguidance of teachers and supervisors in the formal educationunit. This Teaching Assistance activity is carried out for onesemester starting from July 18 to November 4 2022. The authorprovides assistance to grades 5, 6 and children with specialneeds at the Pangkal Pinang Natural School. Mentoring activities in natural schools are carried out by Project Based Learning Learning Model and Thematic Learning Model.